Innovative Learning Model: Improving The Students' Scientific Literacy Of Junior High School - Aprido B. Simamora; Wahono Widodo; I Gusti Made Sanjaya (IJORER : International Journal of Recent Educational Research, 2020)
In the strict challenges faced by society, a paradigm shift is needed in the education system that can provide a set of 21st century skills needed by students to deal with every aspect of global life. One of them is scientific literacy. Unfortunately, the scientific literacy ability of students in Indonesia is still low. The Inquiry and SETS models have been widely applied to improve students' scientific literacy skills. However, weaknesses are found such as: students still cannot use their content knowledge to explain scientific phenomena perfectly; and the need for more in-depth inquiry activities so that students' abilities in designing and evaluating scientific investigations obtain excellent results. Therefore, innovation was created to develop the BRADeR learning model based on consideration of the strengths and weaknesses of the inquiry model and SETS as well as theoretical and empirical support. This research serves as a preliminary study in the process of developing the BRADeR model to improve students' scientific literacy skills. This study includes a needs analysis and literature review. The results show that innovation can be maintained as a basis for developing a hypothetical model of the BRADeR learning model. The syntax of the BRADeR model includes: brainstorming, reading, analyzing, decision making, and reflection. The hypothetical model of the BRADeR learning model must be tested to meet the aspects of validity, practicality, and effectiveness to improve the scientific literacy skills of junior high school students.